Analysis and Prospects for the Development of Regional Energy Integration of the Eurasian Economic Union Countries - Sopilko, Natalya Yuryevna; Myasnikova, Olga Yuryevna; Bondarchuk, Nataliya Vital’evna; Navrotskaia, Natalia Anatolyevna; Migaleva, Tatyana Evgenyevna (International Journal of Energy Economics and Policy, 2020)
In the presented paper, it is proved that a new objective trend appears in the current conditions of Eurasian region development. It will strengthen mutual cooperation between the countries of Eurasia and it will enrich regionalization process in the context of world energy markets restructuring, intensification of competition, deglobalization tendencies and other challenges of the world economy. At the same time, fuel and energy complex (FEC) is becoming the main driving force for the countries of Eurasian region and their further development. The concept of regional energy integration of the Eurasian Economic Union (EAEU) countries is offered in the paper. It’s based on the strategic advantages of economic integration in relation to the fuel and energy complex. Energy potential analysis of the EAEU member countries is performed. The issues of common energy markets formation in the region are considered. The main problems and a number of uncoordinated tasks between the countries participating in integrational process in this area are highlighted in terms of common gas, oil and oil products market formation, although it is noted that development and approval stage of the Programs for such formation is mostly completed. It is expected that these markets will be fully formed by 2025. It was emphasized that energy integration is one of the most important areas for the EAEU countries development, which is expected to bring significant economic benefits in the long-term period. Keywords: regional energy integration, common energy markets, energy potential, the Eurasian Economic Union (the EAEU). JEL Classifications: F02, F63, O13 DOI: https://doi.org/10.32479/ijeep.9806